Identification of c-di-GMP Signaling Components in Xanthomonas oryzae and Their Orthologs in Xanthomonads Involved in Regulation of Bacterial Virulence Expression - Yang, Fenghuan; Xue, Dingrong; Tian, Fang; Hutchins, William; Yang, Ching-Hong; He, Chenyang (Frontiers in Microbiology, 2019)
Xanthomonas oryzae pv. oryzae (Xoo) causes bacterial leaf blight of rice, one of the most devastating bacterial diseases of this staple crop worldwide. Xoo produces a range of virulence-related factors to facilitate its pathogenesis in rice, however, the regulatory mechanisms of Xoo virulence expression have been not fully elucidated. Recent studies have revealed that virulence factor production is regulated via cyclic dimeric guanosine monophosphate (c-di-GMP) signaling pathway that is well conserved in Xoo and other Xanthomonas species. A set of GGDEF, EAL, HD-GYP, and PilZ domain proteins with diverse signal sensory domains for c-di-GMP synthesis, hydrolysis, and binding is encoded in the Xoo genome. Bioinformatic, genetic, and biochemical analysis has identified an array of diguanylate cyclases (DGCs) and phosphodiesterases (PDEs), as well as degenerate GGDEF/EAL, PilZ domain proteins along with a transcription regulator. These signaling components have been characterized to regulate various bacterial cellular processes, such as virulence, exopolysaccharide (EPS) production, biofilm formation, motility, and adaptation at the transcriptional, post-translational, and protein-protein interaction levels. This review summarized the recent progress in understanding the importance and complexity of c-di-GMP signaling in regulating bacterial virulence expression, highlighting the identified key signal elements and orthologs found in Xanthomonads, discussing the diverse functions of GGDEF/EAL/HD-GYP domains, existence of a complicated multifactorial network between DGCs, PDEs and effectors, and further exploration of the new c-di-GMP receptor domains. These findings and knowledge lay the groundwork for future experimentation to further elucidate c-di-GMP regulatory circuits involved in regulation of bacterial pathogenesis.